Gauge invariance for the massive axion - Arias, P. J.; Khoudeir, Adel (Ciencia)
A massive gauge invariant formulation for scalar (o)and antisymmetric (Cmnp) fields with a topological coupling, which provides a mass for the axion field, is considered. The dual and local equivalence with the nongauge invariant proposal is established, but on manifolds with nontrivial topological structure both formulations are not globally equivalent.